PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI MADRASAH ALIYAH AINUL FALAH BAKEONG GULUK-GULUK SUMENEP - Moh. Agus Salim (re-JIEM (Research Journal of Islamic Education Management), 2022)
The quality of learning in educational institutions should be improved because all aspects of achieving student satisfaction can improve school achievement but this is not easy to do but requires the role of the school principal in improving the quality of learning at MA Ainul Flah Bakeong Guluk-Guluk Sumenep. This research includes a qualitative approach with a descriptive type. The results of the study showed that the principal's strategy in improving the quality of learning at MA Ainul Falah Bakeong Guluk-Guluk Sumene first increased teacher professionalism. The second thing is optimizing existing educational facilities and infrastructure in schools. The third is carrying out routine supervision which is carried out every week. Implementation of school principals in improving the quality of learning MA Ainul Falah Bakeong Guluk-Guluk Sumenep Principals as educators (educators), Principals as managers, Principals as supervisors Evaluation of the implementation of school principals in improving the quality of learning Evaluations are conducted in the form of monthly meetings at the end of the semester meeting annual.